Metástases medulares e encefálicas de ependimomas mixopapilares. - Libório, R; Pais, R F; Soares, G B; Rocha, A; Ferreira, F; Garcia, T; Pais, F F (Acta Médica Portuguesa, 2001)
After a brief introduction about the clinical, histological and therapeutic characteristics of myxopapillar spinal ependymoma of cone medullar and filum terminale, three cases with medullar and intracranial seeding of myxopapillar spinal ependymoma are retrospectively reviewed. Surgical resection was total in the child and partial in the adult cases and the histological results were myxopapillar. The diagnosis was made by CT and MRI between 1-2 months before surgical treatment. No extra-neural tumour was found. The mechanisms and factors that influence the seeding of this type of tumour are discussed. The most important literature is reviewed and the cases discussed. The authors stress the importance of surgery on prognosis and the need of an MRI of the whole neural-axis, particularly in children, and subtotal exeresis in adults.